The role of drug treatment and recovery services: an opportunity to address injection initiation assistance in Tijuana, Mexico - Stephanie A. Meyers; Claudia Rafful; Sonia Jain; Xiaoying Sun; Britt Skaathun; Andrew Guise; Patricia Gonzalez-Zuñiga; Steffanie A. Strathdee; Dan Werb; Maria Luisa Mittal (BMC, 2020)
Abstract Background In the U.S. and Canada, people who inject drugs' (PWID) enrollment in medication-assisted treatment (MAT) has been associated with a reduced likelihood that they will assist others in injection initiation events. We aimed to qualitatively explore PWID's experiences with MAT and other drug treatment and related recovery services in Tijuana Mexico, a resource-limited setting disproportionately impacted by injection drug use. Methods PReventing Injecting by Modifying Existing Responses (PRIMER) seeks to assess socio-structural factors associated with PWID provision of injection initiation assistance. This analysis drew on qualitative data from Proyecto El Cuete (ECIV), a Tijuana-based PRIMER-linked cohort study. In-depth qualitative interviews were conducted with a subset of study participants to further explore experiences with MAT and other drug treatment services. Qualitative thematic analyses examined experiences with these services, including MAT enrollment, and related experiences with injection initiation assistance provision. Results At PRIMER baseline, 607(81.1%) out of 748 participants reported recent daily IDU, 41(5.5%) reported recent injection initiation assistance, 92(12.3%) reported any recent drug treatment or recovery service access, and 21(2.8%) reported recent MAT enrollment (i.e., methadone). Qualitative analysis (n = 21; female = 8) revealed that, overall, abstinence-based recovery services did not meet participants' recovery goals, with substance use-related social connections in these contexts potentially shaping injection initiation assistance. Themes also highlighted individual-level (i.e., ambivalence and MAT-related stigma) and structural-level (i.e., cost and availability) barriers to MAT enrollment. Conclusion Tijuana's abstinence-based drug treatment and recovery services were viewed as unable to meet participants' recovery-related goals, which could be limiting the potential benefits of these services. Drug treatment and recovery services, including MAT, need to be modified to improve accessibility and benefits, like preventing transitions into drug injecting, for PWID.